Planet in peril [videorecording (DVD)] - Cooper, Anderson; Gupta, Sanjay, 1969-; Corwin, Jeff (Warner Home Video, 2008)
Anderson Cooper, Dr. Sanjay Gupta and Animal Planet's Jeff Corwin travel to some of the most remote places on Earth. From exposing illegal wildlife trading undercover in Southeast Asia to seeing first-hand the devastating effects of deforestation in Brazil, they have gathered evidence regarding threats to the world's environment.